2018
DOI: 10.1016/j.jaci.2017.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nonmicrobial N-glycolylneuraminic acid protects farmers' children against airway inflammation and colitis

Abstract: In addition to microbial exposure, increased exposure to non-microbial-derived Neu5Gc might contribute to the protective effects associated with the farm environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 49 publications
0
50
0
1
Order By: Relevance
“…PBS buffer was used as a control, since free Neu5Gc would not completely inhibit the diverse reactivities of such antibodies given the potential complexity of Neu5Gc‐antigens on EC. In addition, recent data suggest that Neu5Gc itself may have a direct biological effect on human cells . Details of ECs stimulation procedures are given in the legend of Table S2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBS buffer was used as a control, since free Neu5Gc would not completely inhibit the diverse reactivities of such antibodies given the potential complexity of Neu5Gc‐antigens on EC. In addition, recent data suggest that Neu5Gc itself may have a direct biological effect on human cells . Details of ECs stimulation procedures are given in the legend of Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent data suggest that Neu5Gc itself may have a direct biological effect on human cells. 19 Details of ECs stimulation procedures are given in the legend of Table S2. When mentioned, human pooled sera (dilution of 1:2, 50% of well volume) or TNFα (500 U/mL) were added to the culture medium.…”
Section: Endothelial Cell Stimulationmentioning
confidence: 99%
“…A recent report found that N‐glycolylneuraminic acid (Neu5Gc), a sialic acid found in non‐human mammalian glycoproteins but absent in bacteria, is associated with lower rates of asthma and wheezing in farm children. Levels of anti‐Neu5Gc IgG antibodies correlated positively with living on a farm, and Neu5Gc exerted anti‐inflammatory effects in mouse models of airway inflammation …”
Section: Role Of Innate Immunity In Asthma Protectionmentioning
confidence: 97%
“…Levels of anti-Neu5Gc IgG antibodies correlated positively with living on a farm, and Neu5Gc exerted anti-inflammatory effects in mouse models of airway inflammation. 86…”
Section: Hdm-and Ova-induced Ahr and Bal Eosinophilia As Effectively Asmentioning
confidence: 99%
“…Zudem konnte nachgewiesen werden, dass auch nicht bakterielle Komponenten (z. B. N-Glycolylneuraminsäure) protektiv bei diesen Kindern wirken [9].…”
Section: Merkeunclassified